2007
DOI: 10.1142/s0218396x07003275
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force and Torque on a Solid Elliptic Cylinder

Abstract: Exact expressions for the acoustic radiation torque and force components experienced by elastic cylinders of elliptic cross-section immersed in ideal fluids and placed in a progressive or standing wave field is developed. The classical method of eigen-function expansion and the pertinent boundary conditions are employed to develop analytical expressions in the form of infinite series involving Mathieu and modified Mathieu functions. The complications arising due to the nonorthogonality of angular Mathieu funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…for standing wave (14) (a) (b) 3 shows that the finite element results for very small rigid oblate ellipsoids with zero incidence angle, α=0°, compared well with the results of Marston's formula. This verified the accuracy of the finite element model, and it can be used for different incidence angles and aspect ratios.…”
Section: φ| Sinmentioning
confidence: 56%
See 3 more Smart Citations
“…for standing wave (14) (a) (b) 3 shows that the finite element results for very small rigid oblate ellipsoids with zero incidence angle, α=0°, compared well with the results of Marston's formula. This verified the accuracy of the finite element model, and it can be used for different incidence angles and aspect ratios.…”
Section: φ| Sinmentioning
confidence: 56%
“…He assumed that the length of the cylinder is infinite. He also confirmed that the calculation of acoustic radiation moment yields zero moment for circular cylinders 14 .…”
Section: φ|mentioning
confidence: 60%
See 2 more Smart Citations
“…The aim of this work is therefore directed toward developing a semi-analytical formalism based on the partial wave series expansion method in cylindrical coordinates [10] without any approximations. Another method may consider a wave-basis using infinite series expansions in elliptical Mathieu functions [15][16][17][18][19][20][21], however, the generation and computation of the elliptical functions may not be a straightforward task in numerical implementation.…”
Section: Introductionmentioning
confidence: 99%